Supporting the bereaved relative: reflections on the actor's experience. - Sutton RB (Medical Education, 1998)
For several months 1 and a team of fellow performers were involved, as simulated bereaved relatives, with a research project based in hospitals in the north-west of England. The project, the European Donor Hospital Education Programme, EDHEP (UK), was set up in order to provide a research input into the already established EDHEP in Europe. The programme is designed to develop communication and interpersonal skills among health care workers in Intensive Care/Therapy Units, especially in the breaking of bad news of death to near relatives and in asking consent for the removal of tissues and/or organs for transplantation. The associated research was initiated by an international grouping of clinical psychologists with the purpose of assessing the efficacy of the training schedule Results are expected soon from the main body of research, some aspects of which provide analytical data drawn from encounters between health care professionals and actors as simulated relatives. Here, however, the experiences and feelings of the 'relatives' themselves are described, discussed and reflected upon.